Effects of Source on the Nitrogen Uptake, Allocation Patterns, and Performance of Strawberry (Fragaria × ananassa Duch.): A 15N-Tracer Study - Sirajo Salisu Jibia; Kanokwan Panjama; Chaiartid Inkham; Takashi Sato; Norikuni Ohtake; Soraya Ruamrungsri (Plants)
Nitrogen (N) is an essential determinant of strawberry growth and productivity. However, plants exhibit varying preferences for sources of nitrogen, which ultimately affects its use efficiency. Thus, it is imperative to determine the preferred N source for the optimization of indoor strawberry production. This study employed the 15N-tracer technique to investigate the effects of N sources on N uptake, distribution, and use efficiency, as well as the plants’ growth, for ‘Praratchatan 80’ strawberries in a greenhouse. Five treatments were applied: T1 (5.0 mM 15NO3−), T2 (2.5 mM 15NO3− + 2.5 mM NH4+), T3 (5.0 mM 15NH4+), T4 (2.5 mM 15NH4+ + 2.5 mM NO3−), and T5 (N-free, control) in a completely randomized design. Significant (p < 0.05) differences were observed in N uptake and distribution and total N concentration among the treatments. Sole NH4+ promoted early N uptake and accelerated flowering, while NO3− enhanced vegetative growth and later-stage nitrogen use efficiency (NUE). The application of combined NO3− and NH4+ was most efficacious, balancing the benefits of both N forms. NO3− treatment enhanced 15NUE by 46% compared to NH4+, and mixed N sources demonstrated superior and consistent 15NUE over time. NH4+, alone or with NO3−, expedited flowering by 20 days compared to sole NO3− and N-free treatments. This study elucidates the importance of the sources of N in optimizing strawberry growth and flowering, providing a foundation for developing tailored N-management strategies. Future research should focus on refining mixed N application ratios and timings, exploring molecular mechanisms of N metabolism, and evaluating long-term impacts on strawberry production sustainability.